Síndrome de Burnout en el personal de salud que labora en Medihospital- Loja - Poma Zhingre, Nathalia del Pilar (2022)
The purpose of this research was to determine the prevalence of Burnout Syndrome (BS) in health personnel working at Medihospital in the city of Loja; it was a descriptive, quantitative cross-sectional study. The universe was made up of 34 professionals from Intensive Care, operating room and emergency services, who decided to collaborate voluntarily in this investigation. The technique used was the survey, a questionnaire was applied consisting of 39 questions, and 22 of them correspond to the Maslach Burnout Inventory (MBI) survey- Human Services Survey divided into 3 dimensions, which measure professional exhaustion through emotional fatigue, depersonalization and personal fulfilment, it also had 17 socio-demographic and work variables. The results showed that 73.5% of the staff are female, 64.7% range from 26 to 30 years old, 100% of the population is considered as mixed-race in the canton of Loja, 61.8% indicate that they have no children and 55.9% work as Bachelors in Nursing. A 76.5% have moderate Burnout Syndrome and 23.5 have mild Burnout Syndrome. It is also highlighted that a higher prevalence of Moderate- type (SB) in males (77.8%), aged 20 to 31 years, (76.7%), without a partner, (77.8%) with children (76.9%); and are related to nursing (85.7%). From the results obtained, it can be concluded that all Medihospital health personnel have SB, with moderate-type SB prevailing largely